The Result of the study on feeding young pigs with zeolite mixed feed (Mongolian Journal of Agricultural Sciences, 2021)
In our research experimental trial we have fed the selected 40 head of Landrace piglets, of 3 months old by concentrated mixed feed enreched with 2.0, 4.0 and 6.0 percent of zeolite during 60 days. For the case of the trials when used concentrated feed without zeolite the feed consumption per 1 kg weight gain was 4.7 kg (P